Petroleum Taxes : Trends in Fuel Taxes (and Subsidies) and the Implications - Bacon, Robert (World Bank, Washington, DC, 2012)
Recent World Bank analysis shows that taxes on petroleum products are a critical source of government revenue for low-income countries. And if the experience of industrial countries serves as any guide, the rates of these taxes will have to rise sharply as low-income economies develop. But policymakers must be mindful of how taxes (and subsides) affect the relative prices of fuels, since too large a difference in process between products cab lead to fuel switching and adulteration, adversely affecting the government tax take and pollution levels.